Clinical applications of the VIA Inventory of Strengths with Individuals with Intellectual/Developmental Disabilities. Issue 3 (4th May 2023) - Schwartz, Ariel E.; Caoili, Andrea; Beasley, Joan B.; Kramer, Jessica M.; Kalb, Luther G.
ABSTRACT: Strengths-based clinical practices are critical for supporting the wellbeing of individuals with intellectual and/or developmental disabilities. The VIA Inventory of Strengths ('VIA Survey') is an assessment grounded in positive psychology that may contribute to strengths-based practices. To identify how this assessment is used in clinical practice with individuals with intellectual and/or developmental disabilities, we conducted focus groups (n = 15) with clinicians who have used this survey with this population. We also asked individuals with intellectual and/or developmental disabilities (n = 36) to comment on the process of completing the VIA Survey. We found that clinicians utilize the VIA Survey with individuals with intellectual and/or developmental disability to foster self-esteem and self-understanding, provide a framework for understanding strengths, communicate across service systems and shape strengths-based interventions. Individuals with intellectual and/or developmental disabilities also endorsed use of the survey to increase their self-knowledge and self-esteem. Future research should address accessibility of the survey to foster greater uptake and propose standard protocols for independent survey completion.